2023
DOI: 10.3390/medicina59050857
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Review of the Effects of Extracorporeal Shock Wave Therapy on Stroke Patients: Balance, Pain, Spasticity

Abstract: Stroke remains a leading cause of disability worldwide, with survivors often experiencing impairments in balance, pain, spasticity, and control that limit their ability to perform daily living activities. Extracorporeal shock wave therapy (ESWT) has emerged as a potential treatment modality to improve these outcomes in stroke patients. This review aims to provide a comprehensive examination of the effects of ESWT on stroke patients, focusing on the theoretical background, balance, pain reduction, muscle spasti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Kenmoku T et al found through animal experiments that low-frequency ESWT inhibits acetylcholine binding to receptors and reduces excitability at the neuromuscular junction, thereby relieving muscle spasm (34). Several studies have reported that ESWT improves post-stroke spasticity and enhances motor performance, and has a promising application (35,36). Therefore, the addition of ESWT in combination with BTX-A can be considered in order to obtain a sustained therapeutic effect in a timely manner.…”
Section: Introductionmentioning
confidence: 99%
“…Kenmoku T et al found through animal experiments that low-frequency ESWT inhibits acetylcholine binding to receptors and reduces excitability at the neuromuscular junction, thereby relieving muscle spasm (34). Several studies have reported that ESWT improves post-stroke spasticity and enhances motor performance, and has a promising application (35,36). Therefore, the addition of ESWT in combination with BTX-A can be considered in order to obtain a sustained therapeutic effect in a timely manner.…”
Section: Introductionmentioning
confidence: 99%
“…Rehabilitation post-stroke encompasses physiotherapy, occupational therapy, and speech therapy, which are critical components in restoring patients' functional abilities. According to Lee and Kim, these therapeutic methods can effectively enhance affected individuals' physical and cognitive skills, enabling them to regain independence and improve their overall quality of life [8].…”
Section: Introductionmentioning
confidence: 99%